2018
DOI: 10.1038/s41598-018-23726-3
|View full text |Cite
|
Sign up to set email alerts
|

Insensitivity to atorvastatin is associated with increased accumulation of intracellular lipid droplets and fatty acid metabolism in breast cancer cells

Abstract: Apart from the relevant lipid-lowering effects, statins have demonstrated significant, although heterogeneous, anti-tumor activities in preventing breast cancer (BC) progression. To characterize the critical pathways behind the diverse responses to therapy, we investigated statin-induced changes in regulation of lipid metabolism and abundance of neutral lipid-containing cytoplasmic lipid droplets (LDs) in BC cells displaying different sensitivity to atorvastatin. Following atorvastatin treatment, accumulated L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
(79 reference statements)
3
24
0
Order By: Relevance
“…FTIs have been shown to improve breast cancer prognosis in a phase II clinical trial (Johnston et al, 2003), especially for TNBC (Brewer et al, 2013), and statins have been shown in various breast cancer cell lines to increase apoptosis and decrease the metastatic dissemination of tumors (Van Wyhe et al, 2017). Not all breast cancer cell lines are sensitive to statins, and a very recent study suggests that de novo cholesterol biosynthesis is not required for statin-resistant cell proliferation since these cells increase the exogenous uptake of cholesterol and lipids by increasing the transcription of, for example, 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) (Lettiero et al, 2018). Simvastatin is being evaluated in a phase II clinical trial for metastatic HER2 + breast cancer (Rimawi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…FTIs have been shown to improve breast cancer prognosis in a phase II clinical trial (Johnston et al, 2003), especially for TNBC (Brewer et al, 2013), and statins have been shown in various breast cancer cell lines to increase apoptosis and decrease the metastatic dissemination of tumors (Van Wyhe et al, 2017). Not all breast cancer cell lines are sensitive to statins, and a very recent study suggests that de novo cholesterol biosynthesis is not required for statin-resistant cell proliferation since these cells increase the exogenous uptake of cholesterol and lipids by increasing the transcription of, for example, 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) (Lettiero et al, 2018). Simvastatin is being evaluated in a phase II clinical trial for metastatic HER2 + breast cancer (Rimawi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…From an opposite perspective, these results indicate that the upregulation of LDLR might avert the anti-tumoral effects of statins and raises the question if statin treatment should be avoided in patients with the most apparent LDLR upregulation, or be combined with inhibition of LDLR, a target with emerging therapeutic options [ 69 – 71 ]. Also, preclinical studies have shown a difference in sensitivity to statins between different breast cancer cell lines, where ER-positive cell lines were found to be more insensitive to statins than ER negative [ 72 , 73 ]. The relative insensitivity was found to be associated with increased accumulation of intracellular lipid droplets and fatty acid metabolism [ 73 ] and the upregulation of HMGCR and LDLR mRNA levels, which is thought to be mediated by a dysregulation of the feedback response via the SREBP-2/HMGCR/LDLR axis that counteracts the inhibition of the mevalonate pathway [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were plated at 5,000 cells/well in a 96-MicroWell Nunclon plate (VWR) and left for 24 hours after which they were then treated with drugs for 72 hours, with DMSO as the control. Proliferation was evaluated using the sulforhodamine-B assay as described previously [51]. Concentration response curves and IC50 concentrations for single agent regimens and combination treatments were calculated and analyzed using the drc package (Version 3.0-1) [52] in R (Version 3.3.3) [53].…”
Section: Cell Proliferation Assaymentioning
confidence: 99%